New apigel local use at treatment of oral mucous membrane radiation reactions in patients after head and neck malignant neoplasms radiation therapy = Локальное применение нового апигеля для лечения лучевых реакций слизистой оболочки полости рта у больных после лучевой терапии злокачественных новообразований в области головы и шеи - Kravchenko, L. S.; Bas, N. A.; Coval, S. N.; Davidenko, O. N. (Journal of Education, Health and Sport, 2016)
Kravchenko L. S., Bas N. A., Coval S. N., Davidenko O. N. New apigel local use at treatment of oral mucous membrane radiation reactions in patients after head and neck malignant neoplasms radiation therapy = Локальное применение нового апигеля для лечения лучевых реакций слизистой оболочки полости рта у больных после лучевой терапии злокачественных новообразований в области головы и шеи. Journal of Education, Health and Sport. 2016;6(2):211-222. eISSN 2391-8306. DOI http://dx.doi.org/10.5281/zenodo.46484 http://ojs.ukw.edu.pl/index.php/johs/article/view/3401 https://pbn.nauka.gov.pl/works/716557 The journal has had 7 points in Ministry of Science and Higher Education parametric evaluation. Part B item 755 (23.12.2015). 755 Journal of Education, Health and Sport eISSN 2391-8306 7 © The Author (s) 2016; This article is published with open access at Licensee Open Journal Systems of Kazimierz Wielki University in Bydgoszcz, Poland Open Access. This article is distributed under the terms of the Creative Commons Attribution Noncommercial License which permits any noncommercial use, distribution, and reproduction in any medium, provided the original author(s) and source are credited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/4.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/4.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. The authors declare that there is no conflict of interests regarding the publication of this paper. Received: 05.01.2016. Revised 12.02.2016. Accepted: 21.02.2016. УДК 616.52-006.04:616.31 ЛОКАЛЬНОЕ ПРИМЕНЕНИЕ НОВОГО АПИГЕЛЯ ДЛЯ ЛЕЧЕНИЯ ЛУЧЕВЫХ РЕАКЦИЙ СЛИЗИСТОЙ ОБОЛОЧКИ ПОЛОСТИ РТА У БОЛЬНЫХ ПОСЛЕ ЛУЧЕВОЙ ТЕРАПИИ ЗЛОКАЧЕСТВЕННЫХ НОВООБРАЗОВАНИЙ В ОБЛАСТИ ГОЛОВЫ И ШЕИ Л. С. Кравченко, Н. А. Бас, С. Н. Коваль, О. Н. Давиденко Одесский национальный медицинский университет, Одесса Резюме Использование лучевой терапии для лечения злокачественных новообразований в области головы и шеи наряду с увеличением числа клинических выздоровлений приводит к росту частоты осложнений в ротовой полости. Цель работы оценка эффективности местного применения нового геля «Апиор» в комплексном лечении лучевых осложнений в полости рта у больных с новообразованиями в области головы и шеи после проведенной лучевой терапии. Аппликации геля «Апиор» в комплексном лечении лучевых реакции слизистой оболочки полости рта (СОПР) у пациентов с новообразованиями в области головы и шеи после лучевой терапии благоприятно влияли на объективные и субъективные симптомы лучевых реакций. По сравнению с пациентами, у которых противовоспалительная терапия проводилась традиционными методами, у больных, в схему лечения которых включали местное применение апигеля, отмечено снижение частоты выявления отека и эрозий СОПР, реже наблюдались кровоточивость десен, явления очагового и сливного эпителиита, язвенно-некротические процессы. Отмечено более быстрое уменьшение степени выраженности ксеростомии, что способствовало улучшению гигиенического состояния полости рта, предотвращению вторичной микробной колонизации поврежденных слизистых поверхностей. Аппликации геля «Апиор» сокращали сроки восстановления структурно-функциональной целостности СОПР, что сокращало сроки реабилитации больных. Авторы пришли к выводу, что местное применение геля «Апиор» в комплексной терапии лучевых осложнений в полости рта у больных с новообразованиями в области головы и шеи, подвергшихся лучевому лечению, быстрее снижает выраженность симптомов ксеростомии и лучевых реакций СОПР, купирует их. Включение в схему лечения нового апигеля способствует улучшению гигиенического состояния полости рта, саливации, положительно влияя на неспецифическую резистентность ротовой жидкости и оказывая регенеративное действие, что повышает эффективность лечения и качество жизни больных. Ключевые слова: лучевые реакции слизистой оболочки полости рта, лечение, лучевая терапия, ксеростомия, апигель. NEW APIGEL LOCAL USE AT TREATMENT OF ORAL MUCOUS MEMBRANE RADIATION REACTIONS IN PATIENTS AFTER HEAD AND NECK MALIGNANT NEOPLASMS RADIATION THERAPY L. S. Kravchenko, N. A. Bas, S. N. Coval, O. N. Davidenko Odessa National Medical University, Odessa Summary The use radiotherapy at treatment of malignant neoplasma in the area of the head and neck, together with increased chances for clinical recovery leads to increased rates of radiation complication in oral cavity. The aim of the work is estimation of efficiency of local use new gel “Apior” in complex treatment of radiation complications in cavity mouth in patients with neoplasms in the area of the head and neck who receive radiation therapy. The application of the gel “Apior” in the complex therapy of radiation reactions of the oral mucous membrane (OMM) in patients with neoplasms in the area of the head and neck after radiation treatment influenced favorably the objective and subjective symptoms of radiation reactions. In comparison with patients who were given local anti-inflammatory therapy by traditional methods, the patients with application of the apigel were observed to have fast healing of edema, OMM erosion, there were less often marked gingival hemorrhage, phenomena of local and confluent epitheliitis, ulcerotic-necrotic processes. There was observed reduction in the xerostomia level manifestation that promoted improvement of the hygienic condition of the oral cavity, prevention of the secondary microbic colonization of the damaged mucous surfaces. The application of the gel “Apior” reduced terms of restoration of the structural-functional integrity of OMM that promoted rehabilitation of the patients. Authors conclude that gel “Apior” local application in the complex therapy of radiation complications in cavity mouth in patients with neoplasms in the area of the head and neck who underwent radiation treatment reduces symptoms of xerostomia and radiation reactions OMM more quickly and stops them. Inclusion of the apigel in the scheme of treatment improvement of the hygienic condition of the oral cavity, of the salivary secretion, which have positive influence on nonspecific resistance in oral liquid and restored of the structural integrity of OMM, that improves quality of treatment and life of the patients. Key words: radiation reactions the oral mucous membrane, treatment, radiation therapy, xerostomia, apigel. Резюме ЛОКАЛЬНЕ ЗАСТОСУВАННЯ НОВОГО АПІГЕЛЮ ДЛЯ ЛІКУВАННЯ ПРОМЕНЕВИХ РЕАКЦІЙ СЛИЗОВОЇ ОБОЛОНКИ ПОРОЖНИНИ РОТА У ХВОРИХ ПІСЛЯ ПРОМЕНЕВОЇ ТЕРАПІЇ ЗЛОЯКІСНИХ НОВОУТВОРЕНЬ В ДІЛЯНЦІ ГОЛОВИ ТА ШИЇ. Використання променевої терапії для лікування злоякісних новоутворень в ділянці голови та шиї разом зі збільшенням числа клінічних видужань призводить до зростання частоти ускладнень в ротовій порожнині. Мета роботи - оцінка ефективності місцевого застосування нового гелю «Апіор» в комплексному лікуванні променевих ускладнень в порожнині рота у хворих з новоутвореннями в ділянці голови та шиї після проведеної променевої терапії. Аплікації гелю «Апіор» в комплексному лікуванні променевих реакції слизової оболонки порожнини рота (СОПР) у пацієнтів з новоутвореннями в ділянці голови та шиї після променевої терапії сприятливо впливали на об’єктивні і суб’єктивні симптоми променевих реакцій. У порівнянні з пацієнтами, у яких протизапальна терапія проводилася традиційними методами, у хворих, в схему лікування яких включали місцеве застосування апігеля, відзначено зниження частоти виявлення набряку і ерозій СОПР, рідше спостерігалися кровоточивість ясен, явища осередкового і зливного епітеліїту, виразково-некротичні процеси. Відзначено швидкіше зменшення ступеня вираженості ксеростомії, що сприяло поліпшенню гігієнічного стану порожнини рота, запобігання вторинної мікробної колонізації пошкоджених слизових поверхонь. Аплікації гелю «Апіор» скорочували терміни відновлення структурно-функціональної цілісності СОПР, що скорочувало терміни реабілітації хворих. Автори дійшли висновку, що місцеве застосування гелю «Апіор» в комплексній терапії променевих ускладнень в порожнині рота у хворих з новоутвореннями в ділянці голови та шиї, які зазнали променевого лікування, швидше знижує вираженість симптомів ксеростомії та променевих реакцій СОПР, усуває їх. Включення в схему лікування нового апігеля сприяє поліпшенню гігієнічного стану порожнини рота, салівації, позитивно впливаючи на неспецифічну резистентність ротової рідини і надаючи регенеративну дію, що підвищує ефективність лікування і якість життя хворих. Ключові слова: променеві реакції слизової оболонки порожнини рота, лікування, променева терапія, ксеростомія, апігель.